2017
DOI: 10.1590/0103-8478cr20160722
|View full text |Cite
|
Sign up to set email alerts
|

Drying and pickling on phenols, capsaicinoids, and free radical-scavenging activity in Anaheim and Jalapeño peppers

Abstract: The effects of sun-drying, air-drying and pickling processes on phenol and capsaicinoid contents, and free radical-scavenging activity [2,2-diphenyl-1-picrylhydrazyl (DPPH), and 2,2′-azino-bis 3-ethylbenzthiazoline-6-sulphonic acid (ABTS)] in Anaheim (red) and Jalapeño peppers were evaluated. Sun-drying process in Anaheim pepper caused the highest phenols retention (100%), and the free radical-scavenging activity (100%) when compared with air-drying (80%). Pickling process in Jalapeño pepper caused a moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…The AC of the dried samples showed a similar trend to that of the TPC and decreased markedly when compared to fresh sample. This was in accordance with Blanco-Rios et al (2017), who reported a decrease in the antioxidant activity of red pepper after hotair drying due to the result of the oxidation of phenolic compounds. A similar result was observed by Reyes et al (2011) in apple.…”
Section: Total Polyphenol Content and Antioxidant Capacitysupporting
confidence: 92%
See 1 more Smart Citation
“…The AC of the dried samples showed a similar trend to that of the TPC and decreased markedly when compared to fresh sample. This was in accordance with Blanco-Rios et al (2017), who reported a decrease in the antioxidant activity of red pepper after hotair drying due to the result of the oxidation of phenolic compounds. A similar result was observed by Reyes et al (2011) in apple.…”
Section: Total Polyphenol Content and Antioxidant Capacitysupporting
confidence: 92%
“…A similar result was observed by Reyes et al (2011) in apple. Blanco-Rios et al (2017) also found significant correlations between the TPC and antioxidant activity in red peppers. As seen in Table 6, pretreatment, but not temperature, significantly affected the AC of the dried red peppers.…”
Section: Total Polyphenol Content and Antioxidant Capacitymentioning
confidence: 66%
“…Barros et al (2011) reported trolox equivalent antioxidant capacity (TEAC) of raw, boiled and roasted chestnuts between the ranges of 0.47 ± 0.01 and 1.04 ± 0.10 mmol trolox/kg and indicated a decrease in boiled and roasted chestnuts compared to the raw one, in great accordance with current findings. In previous literature similar decrement of antioxidant capacity in the pickles compared to the raw material was reported by Ganguli et al (2007) in mushroom and Blanco-Rios et al (2017) in jalapeno pepper pickles respectively. The lower AC value of the products compared to the raw material could be explained by the enzymatic, chemical, or thermal degradation of bioactive components as a result of the heat treatment as well as the oxidation of phenolic compounds (Nicoli et al, 1999).…”
Section: Antioxidant Capacitysupporting
confidence: 81%
“…The Serrano sample had the highest total capsaicinoid content (3,330.9 μg/g dw), which is similar to the result of BRPS, the capsaicin, and nordihydrocapsaicin contents were lower than that of BRPS, whereas the dihydrocapsaicin content was higher than that of BRPS (Table 2). [45] Blanco-Rios et al [46] found that the capsaicin and dihydrocapsaicin contents of the different dried red peppers were 17.91-76.71 and 9.73-25.36 μg/g dry weight, respectively, which were approximately 30-120 and 50-130-folds lower than those of BRPS. Ku et al [28] have determined the capsaicin and dihydrocapsaicin contents of 20 domestic varieties of red pepper seeds cultivated in Korea and four foreign varieties of samples cultivated in New Mexico, USA.…”
Section: Capsaicinoid Contents Determined By Hplc Analysismentioning
confidence: 98%